Association of substance use characteristics and future homelessness among emergency department patients with drug use or unhealthy alcohol use: Results from a linked data longitudinal cohort analysis. Issue 1 (1st December 2022) - Yoo, Ruth; Krawczyk, Noa; Johns, Eileen; McCormack, Ryan P.; Rotrosen, John; Mijanovich, Tod; Gelberg, Lillian; Doran, Kelly M.
Abstract: Background: Homelessness and substance use are intricately related, and both are prevalent among emergency department (ED) patients. This study examined the longitudinal association of substance use characteristics with future homeless shelter entry among ED patients with any drug use or unhealthy alcohol use. Methods: We present results from a longitudinal cohort study of public hospital ED patients who screened positive for drug use or unhealthy alcohol use and who were not homeless at their baseline (index) ED visit. The primary outcome was homeless shelter entry within 12 months of baseline, ascertained in city homeless shelter administrative data. Primary independent variables of interest were alcohol use severity (AUDIT), drug use severity (DAST-10), and types of drugs used, as reported on baseline survey questionnaires. Results: Analyses included 1, 210 ED patients. By 12 months following the baseline ED visit, 114 (9.4%) had entered a homeless shelter. Among patients with the most severe problems related to drug use (DAST-10 score 9–10), 40.9% entered a shelter within 12 months. Past shelter use was the strongest predictor of future shelter entry; once adjusting for historic shelter use the relationship of AUDIT and DAST-10 scores with future shelter entry was no longer statistically significant in multivariable models. Conclusions: ED patients with past year drug use or unhealthy alcohol use had relatively high likelihood of future shelter entry. Risk for homelessness should be addressed in future interventions with this population. Findings illustrate the complexity of relationships between substance use and homelessness.